Global Change and Sustainable Development in Mountain Regions - Proceedings of the COST Strategic Workshop - Jandl, Robert (alpine space - man and environment, 2009)
The Strategic Workshop "Global Change and Sustainable Development in Mountain Regions" was convened at the Congress Hall of Innsbruck, Austria, from April 7-9, 2008. The event attracted more than 350 scientists, experts, practitioners, students, and scholars from 29 European and 10 non-European countries. The book is structured in accordance to the conference agenda. In 13 chapters it presents contributions to basic research, to socio-economic topics and regional studies. The risks related to climate change are also addressed as water issues, high elevation ecosystems and monitoring methods. Forestry, tourism and ecosystem services of mountains are most important to evaluate the economy and the output of mountain systems. Mountains all over the word are challenged by global change. This is illustrated by regional examples of the Carpathians, the Andes, the Rocky Mountains and the Pacific North West of Canada.